Evaluation of associations of GSTM1/GSTT1 null genotypes with the susceptibility to age-related macular degeneration, a meta-analysis: GSTT1/GSTM1 polymorphisms and ARMD - Saadat, Mostafa (Scripta Medica, 2021)
Background: The relationship between glutathione S-transferase M1 (GSTM1) and T1 (GSTT1) null genotypes (homozygotes for the null alleles) and the susceptibility to age-related macular degeneration (ARMD) have been reported and revealed inconsistent results. Therefore, the current meta-analysis was carried out.Methods: Eligible published articles (before December 2020) were found by searching 8 databases. The data was extracted from articles. The heterogeneity across studies was estimated using Q and I2 statistics and the odds ratios (ORs) and its 95 % confidence intervals (95 % CI) were estimated.Results: In total, 6 independent studies including 1089 participants (634 controls and 455 patients) were used in the current study. There was no heterogeneity between studies for both polymorphisms. Statistical analysis showed that the null genotypes of the GSTM1 (OR = 1.18, 95 % CI: 0.91 - 1.53, p = 0.191) and GSTT1 (OR = 0.84, 95 % CI: 0.60 - 1.18, p = 0.328) loci were not correlated with the susceptibility to ARMD.Conclusion: The GSTT1 and GSTM1 genetic polymorphisms did not associated with the risk of ARMD in Caucasian populations.
Keywords: GSTM1; GSTT1; Age-related macular degeneration; Meta-analysis